Bioinformatics computing - Bryan Bergeron, M.D; Bryan Bergeron, M.D (New Delhi Prentice-hall of india)
bioinformatics of computing is a practical guide to computing in the burgeoning fields of informatics
central dogma databases networks search engines
Keywords: central dogma,databases,networks,search engines